Atmospheric sea-salt and halogen cycles in the Antarctic. Issue 10 (4th August 2020) - Hara, Keiichiro; Osada, Kazuo; Yabuki, Masanori; Matoba, Sumito; Hirabayashi, Motohiro; Fujita, Shuji; Nakazawa, Fumio; Yamanouchi, Takashi
Abstract : Atmospheric sea-salt and halogen cycles play important roles in atmospheric science and chemistry including cloud processes and oxidation capacity in the Antarctic troposphere. Abstract : Atmospheric sea-salt and halogen cycles play important roles in atmospheric science and chemistry including cloud processes and oxidation capacity in the Antarctic troposphere. This paper presents a review and summarizes current knowledge related to sea-salt and halogen chemistry in the Antarctic. First, presented are the seasonal variations and size distribution of sea-salt aerosols (SSAs). Second, SSA origins and sea-salt fractionation on sea-ice and ice sheets on the Antarctic continent are presented and discussed. Third, we discuss SSA release from the cryosphere. Fourth, we present SSA dispersion in the Antarctic troposphere and transport into inland areas. Fifth, heterogeneous reactions on SSAs as a source of reactive halogen species and their relationship with atmospheric chemistry are shown and discussed. Finally, we attempt to propose an outlook for obtaining better knowledge related to sea-salt and halogen chemistry and their effects on the Antarctic and the Arctic.